HUMOUR AND LINGUISTIC FEATURES OF AFRICAN FOLKTALES - Patrick, Charles Alex (LLT Journal: A Journal on Language and Language Teaching, 2024)
African folktales manifest intricate and peculiar linguistic features, making their performance remarkable and invigorating. This paper explores the dual impact of humour and linguistic features on the written and performative nature of African folktales, arguing that the linguistic features of African folktales are imbued with humour which enlivens their oral performances. The data utilised in this study were harvested from folktales across Africa, including some collected during oral performances in Ipe-Akoko in Ondo State, Nigeria. Ten folktales were purposely selected from written sources while two were collected during performance. The performances of the folktales fostered a comprehensive understanding of the impact that the linguistic features laced with humour have on the audience. The data were subjected to critical reading using content analysis. The theoretical framework of this study was anchored in Henri Bergson’s theoretical work; Laughter: An Essay on the Meaning of Comic (1923). The results showed that many African folktales manifest sterling linguistic devices laced with humour that embellish the narrative structure of the written folktales while enhancing the performative experience of the audience during the performance in Ipe-Akoko. The study concluded that folktales function as a means of galvanising and lubricating African languages and other verbal components whenever they seem to be inadequate.